PENGARUH KUALITAS JASA PERBANKAN TERHADAP LOYALITAS NASABAH DI BANK RAKYAT INDONESIA SURABAYA - Yusak Anshori (Journal of Business & Banking, 2011)
It is advisable that the banks should try hard to maximize their services for their customers.By doing so, it can also improve their customers loyalty. The purpose of this study is toanalyze whether the quality of services consist of tangibles, reliability, responsiveness,assurance and empathy has significant effect on customer loyalty. The data were collected bymeans of survey method by distributing the questionnaires to Britama savings customers inSurabaya. From the total of 366 questionnaires which were spread out, only 218 that couldbe used. The tool of study analysis was using multiple linear regression, overall responsesprovided by customers of BRI conferred a positive assessment regarding the quality ofservices available. The results of this research showed that the direct evidence, reliability,assurance and empathy have a significant influence on the customer loyalty at Bank RakyatIndonesia (BRI) Surabaya. It also can be used to improve the quality of services by makingthe right marketing strategy in order to maintain customer loyalty